2020
DOI: 10.1016/j.cmrp.2020.05.003
|View full text |Cite
|
Sign up to set email alerts
|

COVID 19 can spread through breathing, talking, study estimates

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 1 publication
0
39
0
3
Order By: Relevance
“…More recently, the concerns over airborne infections have resurfaced with the COVID-19 pandemic caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV2). It was reported that bioaerosols carrying SARS-CoV2 could remain suspended in the air for a few hours [ 6 ]. Several groups have also detected SARS-CoV2 RNA in air samples collected in hospital rooms, supporting the potential transmission of SARS-CoV2 via aerosols in indoor environments [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the concerns over airborne infections have resurfaced with the COVID-19 pandemic caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV2). It was reported that bioaerosols carrying SARS-CoV2 could remain suspended in the air for a few hours [ 6 ]. Several groups have also detected SARS-CoV2 RNA in air samples collected in hospital rooms, supporting the potential transmission of SARS-CoV2 via aerosols in indoor environments [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The transmission of COVID-19 takes place by inhaling the respiratory droplets coming from the coughing or sneezing of an infected person. 2 It is unknown when COVID-19 spread to Bangladesh. However, the first three cases were reported on March 8, 2020.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid spread of COVID-19, self-protection has become crucial to avoid contracting this disease. As a highly infectious disease, the two main routes of transmission include direct transmission (e.g., spraying droplets emitted from aerosolized particles through sneezing, coughing or talking), and indirect transmission (contact with surfaces that contain the virus or objects that have been in contact with an infected individual) (Liu, 2020;Ningthoujam, 2020;Tomar and Gupta, 2020). However, the former has been documented to be a more prevalent form of transmission, so an effective mask must be worn to obstruct the transmission of the virus and block its spread when conducting daily life activities (Bałazy et al, 2006;MacIntyre and Chughtai, 2020).…”
Section: Introductionmentioning
confidence: 99%